2005
DOI: 10.1002/smll.200500009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes for Microelectronics?

Abstract: Despite all prophecies of its end, silicon-based microelectronics still follows Moore's Law and continues to develop rapidly. However, the inherent physical limits will eventually be reached. Carbon nanotubes offer the potential for further miniaturization as long as it is possible to selectively deposit them with defined properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 10 publications
1
56
0
Order By: Relevance
“…Therefore, we measured the electrical resistivity of a freestanding individual nanofiber using methods described in the relevant literature. [28,29] After spin-coating a nanofiber suspension onto Au/Ti electrodes, we confirmed that an individual fibre had bridged the electrode gap (500 nm) using FE-SEM. We then obtained the intrinsic resistivity of an individual nanofiber from a linear current-voltage relation up to 1 V. As shown in Figure 3 b, the electrical resistivity at room temperature of the individual as-grown carbon nanofibers were extremely high (ca.…”
supporting
confidence: 52%
“…Therefore, we measured the electrical resistivity of a freestanding individual nanofiber using methods described in the relevant literature. [28,29] After spin-coating a nanofiber suspension onto Au/Ti electrodes, we confirmed that an individual fibre had bridged the electrode gap (500 nm) using FE-SEM. We then obtained the intrinsic resistivity of an individual nanofiber from a linear current-voltage relation up to 1 V. As shown in Figure 3 b, the electrical resistivity at room temperature of the individual as-grown carbon nanofibers were extremely high (ca.…”
supporting
confidence: 52%
“…Constituting carbon-based nanoscale diodes or transistors has, thus, become one of the main topics in nanotube-based electronics. 28,29 Doping of some kinds of heteroatoms into carbon nanotubes may lead to the modification of electron structure and, as a result, the formation of electron-excess n-type (e.g., nitrogen-doped) or electron-deficient p-type (e.g., boron-doped) semiconducting nanotubes. [30][31][32][33] Provided that one can control at the nanometer level the position and distribution of such heteroatoms as N (nitrogen) and B (boron) in carbon nanotubes, various types of nanostructured junctions with controlled electronic properties would be possibly prepared.…”
Section: Synthesis Of Various Types Of Carbon Nanotubesmentioning
confidence: 99%
“…[DOI: 10.1143/JJAP.45.L190] KEYWORDS: nanowire, silicon, growth mechanism, VLS Silicon nanowires have attracted significant attention in the last few years owing to their reduced dimensionality, which is of interest in both fundamental and applied studies. On a fundamental side, the nanoscale dimensions lead to inherently quantum mechanical effects such as the Coulomb blockade effect.1,2) On the applied side silicon nanowires hold the promise for the realization of high device density chips 3,4) and complementary metal-oxide-semiconductor (CMOS) technology compatibility. To date silicon nanowires have been synthesized and a wide range of electronic devices [5][6][7][8][9][10][11] with nanoscale dimensions, highly sensitive biochemical sensors, dye sensitized solar cells as well as novel thermo-electric properties have been demonstrated.…”
mentioning
confidence: 99%